Clove flower powder (Syzygium Aromaticum) as an alternative plant controlling Aedes Aegypti larvae - Ummi Kalsum Supardi; Rizka Suciyati Buano; Nadratillah Istiqomah Alhadar; Mariyana Ismail; Rafiqa Imran; Widya Putri Avilliani (CORE JOURNAL, 2022)
Dengue Hemorrhagic Fever (DHF) is still one of the most important health problems in Indonesia. Indonesia is a country with the highest dengue cases in Southeast Asia. The purpose of this study was to determine the effectiveness of clove flower powder (Syzygium aromaticum) as a medium in killing Aedes aegypti larvae. This type of research is a simple experimental study with a post test only group control design. This research was conducted to determine the effectiveness of clove powder in killing Aedes Aegypti larvae using doses of 2 mg/10L, 4 mg/10L, 6 mg/10L, 8 mg/10L and 10 mg/10L. Data collection techniques are carried out by making observations, namely by making direct observations. The results showed that each level of the test material (P1, P2, P3, P4, and P5) within 1x24 hours of observation showed a significant difference in the mortality of Aedes Aegypti larvae. The conclusion of this study was that clove powder (Syzygium Aromaticum) was effective in killing Aedes Aegypti larvae with varying results according to the level. Even so, it is still necessary to carry out further research by testing more local plant species as a medium that can kill Aedes Aegypti larvae by paying attention to environmental factors and it is advisable to examine the comparison between Zanzibar clove flowers and ordinary clove flowers